The Effect of Pocket Money Management and Future Orientation on the Saving Behavior of Yogyakarta Students with Saving Intention as a Mediation Variable and Financial Attitude as a Moderation Variable - Balqis Syathiri; Aula Ahmad Hafidh Saiful Fikri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to find out (1) the influence of Pocket Money on Saving Behavior, (2) the influence of Future Orientation on Saving Behavior, (3) the influence of Saving Intention on Saving Behavior, (4) the influence of Pocket Money on Saving Behavior mediated by the Saving Intention variable, (5) the influence of Future Orientation on Saving Behavior mediated by the Saving Intention variable, (6) the effect of Saving Intention on Saving Behavior moderated by the Financial Attitude variable. This study is a quantitative research that analyzes whether or not there is a causal relationship between the variables described. The population in this study is 129,853 active students who are pursuing higher education in the Special Region of Yogyakarta. The sample of this study is 399 students who were selected through nonprobability sampling with the research sample taken using convenience sampling techniques. Data was collected through questionnaires, interviews, and analyzed using structural equation modeling (SEM) to simultaneously test all relationships. The results of the study showed that (1) Pocket Money had a positive effect on Saving Behavior, (2) Future Orientation had a positive effect on Saving Behavior, (3) Saving Intention had a positive effect on Saving Behavior, (4) Saving Intention was able to mediate the influence of Pocket Money on Saving Behavior, (5) Saving Intention is able to mediate the influence of Future Orientation on Saving Behavior mediated by the Saving Intention variable, (6) Financial Attitude is able to moderate the influence of Saving Intention on Saving Behavior.